Using concept mapping to develop a human rights based indicator framework to assess country efforts to strengthen rehabilitation provision and policy: the Rehabilitation System Diagnosis and Dialogue framework (RESYST) - Dimitrios Skempes; John Melvin; Per von Groote; Gerold Stucki; Jerome Bickenbach (BMC, 2018)
Abstract Background Rehabilitation is crucial for the realization of the right to health and a proper concern of global health. Yet, reliable information to guide rehabilitation service planning is unavailable in many countries in part due to the lack of appropriate indicators. To ensure universal health coverage and meet the central imperative of "leaving no one behind" countries must be able to assess key aspects of rehabilitation policy and provision and monitor how they have discharged their human rights responsibilities towards those most disadvantaged, including people with disability. This article describes the process of developing an expert guided indicator framework to assess governments' efforts and progress in strengthening rehabilitation in line with the Convention on the Rights of Persons with Disabilities. Methods A systems methodology - concept mapping - was used to capture, aggregate and confirm the knowledge of diverse stakeholders on measures thought to be useful for monitoring the implementation of the Convention with respect to health related rehabilitation. Fifty-six individuals generated a list of 107 indicators through online brainstorming which were subsequently sorted by 37 experts from the original panel into non overlapping categories. Forty-one participants rated the indicators for importance and feasibility. Multivariate statistical techniques where used to explore patterns and themes in the data and create the indicators' organizing framework which was verified and interpreted by a select number of participants. Results A concept map of 11 clusters of indicators emerged from the analysis grouped into three broader themes: Governance and Leadership (3 clusters); Service Delivery, Financing and Oversight (6 clusters); and Human Resources (2 clusters). The indicator framework was comprehensive and well aligned with the Convention. On average, there was a moderately positive correlation between importance and feasibility of the indicators (r = .58) with experts prioritizing the indicators contained in the clusters of the Governance and Leadership domain. Two of the most important indicators arose from the Service Delivery, Financing and Oversight domain and reflect the need to monitor unmet needs and barriers in access to rehabilitation. In total, 59 indicators achieved above average score for importance and comprised the two-tiered priority set of indicators. Conclusion Concept mapping was successful in generating a shared model that enables a system's view of the most critical legal, policy and programmatic factors that must be addressed when assessing country efforts to reform, upscale and improve rehabilitation services. The Rehabilitation Systems Diagnosis and Dialogue framework provides a data driven basis for the development of standardized data collection tools to facilitate comparative analysis of rehabilitation systems. Despite agreement on the importance and feasibility of 59 indicators, further research is needed to appraise the applicability and utility of the indicators and secure a realistic assessment of rehabilitation systems.